UBE3A and MCM6 synergistically regulate the proliferation and migration of lung adenocarcinoma cells - Yanyan Luo; Yun Yang; Cong Yang; Chuanyin Li; Ronggui Hu; Wujun Geng; Xianhui Kang; Hai Lin (FEBS Open Bio, 2023)
Lung cancer is a leading cause of mortality worldwide and shows substantial clinical and biomolecular heterogeneity. Currently, specific therapeutic strategies are lacking, so effective drug targets are urgently needed. E6AP/UBE3A is a multifaceted ubiquitin ligase that controls various signaling pathways implicated in neurological diseases and various cancers; however, its role in lung cancer is incompletely understood. Here, MCM6 was identified as an interacting partner of E6AP using the yeast two‐hybrid assay. MCM2 and MCM4 were then shown to interact with E6AP. E6AP knockout enhanced the ubiquitination of MCM2/4/6, suggesting that E6AP was not the E3 ubiquitin ligase for these three MCM proteins. Ablation of E6AP inhibited proliferation and migration, but had no significant effect on apoptosis in A549 and H1975 cells, and proliferation and migration inhibition was also observed in MCM6 knockdown cells. Furthermore, ablation of MCM6 and E6AP synergistically suppressed the proliferation and migration of A549 and H1975 cells. To verify the above findings in vivo, we established tumor models in nude mice and identified that the tumorigenicity of human lung adenocarcinoma (LUAD) cells was synergistically regulated by MCM6 and E6AP. Moreover, the expression levels of MCM6 and E6AP were higher in LUAD tissues than in adjacent tissues. Furthermore, the expression levels of MCM6 and E6AP were positively correlated in human LUAD samples. Thus, our study suggests that the interaction of E6AP and MCM proteins plays an important role in the progression of LUAD, which might offer potential therapeutic targets for cancer treatment.